Formulation and physical characteristics of ready-to-drink chocolate beverages with the addition of xanthan gum: Formulasi Dan Karakteristik Fisik Minuman Cokelat Ready-To-Drink Dengan Penstabil Xanthan Gum - Esa, Sonia Dora Febri; Sari, Anjar Ruspita; Sabarisman, Iman; Setyowati, Rini (JITIPARI, 2025)
Ready-to-drink (RTD) chocolate beverages are increasingly popular, yet traditional formulations often contain dairy components while some consumers are lactose intolerance. The primary challenges in RTD chocolate beverages include achieving acceptable flavor profiles and managing cocoa powder precipitation. This study aimed to formulate a non-dairy ready-to-drink chocolate beverage using a hedonic test and  enhance its physical stability through varied xanthan gum concentrations applying Completely Randomized Design (CRD).A hedonic test involving 30 untrained respondents determined the most preferred formula with the highest preference level (3.7), which consisted of 40% local cocoa powder from Kulon Progo, Yogyakarta, 15% commercial cocoa powder, and 45% castor sugar. Stability analysis involved incorporating xanthan gum at concentrations of 0.1%, 0.15%, and 0.2% (w/v). Results demonstrated that 0.2% xanthan gum concentration yielded the highest viscosity (98 N.s/m²), significantly differing from the control. The lowest precipitation was observed at 0.2% concentration (p-value 0.048). Particle size analysis revealed progressive reduction from 21 μm to 5 μm with increasing xanthan gum concentration. The study conclusively identified 0.2% (w/v) xanthan gum as the most effective concentration for improving chocolate beverage stability, offering a promising approach for developing innovative, dairy-free RTD products.